2018
DOI: 10.3390/foods7040053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Codium tomentosum Extract in the Properties of Alginate and Chitosan Edible Films

Abstract: The growing search for natural alternatives to synthetic food packaging materials and additives has increased, and seaweed extracts’ bioactivity has made them suitable candidates for incorporation in novel edible films. This study aims to investigate the effect of Codium tomentosum seaweed extract (SE) incorporation in alginate and chitosan edible films. Alginate- and chitosan-based films with and without the incorporation of 0.5% SE were characterized according to their physical, optical, mechanical, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 51 publications
7
29
1
Order By: Relevance
“…Overall, the hereby described results are in accordance with that of Odila Pereira, Soares, Sousa, Madureira, Gomes, and Pintado [3], in terms of FTIR spectra in regards to the spectra of WPI-based film formulations. Augusto et al [58], who made ALG edible films with Codium tomentosum seaweed extract, also reported no significant differences between the FTIR spectra of an ALG film with and without seaweed extract in terms of wavenumber absorbance.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Measurementsmentioning
confidence: 97%
“…Overall, the hereby described results are in accordance with that of Odila Pereira, Soares, Sousa, Madureira, Gomes, and Pintado [3], in terms of FTIR spectra in regards to the spectra of WPI-based film formulations. Augusto et al [58], who made ALG edible films with Codium tomentosum seaweed extract, also reported no significant differences between the FTIR spectra of an ALG film with and without seaweed extract in terms of wavenumber absorbance.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Measurementsmentioning
confidence: 97%
“…To evaluate the radical stability, a volume of 150 µL of ethanol was added to 15 microplate wells followed by addition of 150 µL of DPPH • diluted solution during an incubation period of 120 min at room temperature, with absorbance measured at 517 nm every 5 min. For evaluation of the radical scavenging potential, a volume of 150 µL of C. tomentosum lipid extract (50,100,200, 500 µg mL −1 in ethanol) and 150 µL of Trolox standard solution (10,25,50, and 75 µg mL −1 in ethanol) were placed in each well followed by addition of 150 µL of DPPH • diluted solution, and again an incubation period of 120 min, with absorbance measured at 517 nm every 5 min. Control lipid extracts were tested by replacing 150 µL of DPPH • diluted solution by 150 µL of ethanol.…”
Section: -Diphenyl-1-picrylhydrazyl Radical Assay-dpph Radical Scavementioning
confidence: 99%
“…It presents in its composition lipids with nutritional and health benefits [21], and organic acids and volatile compounds with antioxidant properties [13]. Organoleptic properties and composition of the genus Codium make these macroalgae appreciated in the gourmet cuisine and cosmetic industry, with the latest using its extracts as a skin protecting agent in commercial formulations [21,24,25]. Lipidomic characterization showed that C. tomentosum has a high lipid content (~10%) in comparison to other seaweeds, which usually display between 1% and 2% of lipid content [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…A Fourier transform infrared spectrometer (PerkinElmer, Fremont, California, USA) was used to detect functional groups of film samples and possible changes caused by addition of carvacrol. The film was ground into a fine powder, quickly frozen with liquid nitrogen, and pressed into sheets; the scanning range was 400-4000 cm −1 at a resolution of 4 cm −1 with 32 scans [58].…”
Section: Ftirmentioning
confidence: 99%